2019
DOI: 10.1101/770826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal complexity of fMRI is reproducible and correlates with higher order cognition

Abstract: In 2014, McDonough and Nashiro [1] derived multiscale entropy -a marker of signal complexity-from resting state functional MRI data (rsfMRI), and found that functional brain networks displayed unique multiscale entropy fingerprints. This is a finding with potential impact as an imaging-based marker of normal brain function, as well as pathological brain dysfunction. Nevertheless, a limitation of this study was that rsfMRI data from only 20 healthy individuals was used for analysis. To overcome this limitation,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 94 publications
4
21
0
Order By: Relevance
“…The present study revealed that better gf task performance was associated with greater left frontal AUC and AvgEnt , higher parietal AvgEnt , and larger left frontal relative to right frontal AvgEnt (Table 2, Figure 9). These results are partially congruent with previous evidence from resting‐state fMRI studies (McDonough & Nashiro, 2014; Omidvarnia et al, 2019; Saxe, Calderone, & Morales, 2018) demonstrating increased brain entropy in the prefrontal cortex, inferior temporal lobes and cerebellum associated with higher gf (Saxe et al, 2018), a positive relationship of fluid intelligence with the complexity of resting‐state networks including the FPN (Omidvarnia et al, 2019) or with the temporal variability of the middle frontal, inferior parietal and visual cortices (Yang et al, 2019). A higher intelligence level also turned out to coexist with more efficient organization of the whole‐brain network (van den Heuvel et al, 2009) or mainly the FPN (Duncan, 2010; Langer et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study revealed that better gf task performance was associated with greater left frontal AUC and AvgEnt , higher parietal AvgEnt , and larger left frontal relative to right frontal AvgEnt (Table 2, Figure 9). These results are partially congruent with previous evidence from resting‐state fMRI studies (McDonough & Nashiro, 2014; Omidvarnia et al, 2019; Saxe, Calderone, & Morales, 2018) demonstrating increased brain entropy in the prefrontal cortex, inferior temporal lobes and cerebellum associated with higher gf (Saxe et al, 2018), a positive relationship of fluid intelligence with the complexity of resting‐state networks including the FPN (Omidvarnia et al, 2019) or with the temporal variability of the middle frontal, inferior parietal and visual cortices (Yang et al, 2019). A higher intelligence level also turned out to coexist with more efficient organization of the whole‐brain network (van den Heuvel et al, 2009) or mainly the FPN (Duncan, 2010; Langer et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In all of these cases, the mMSE vectors were stable and characterized by a skewed inverted‐U shape across time scales, which is typical for EEG and MEG signals (Costa et al, 2005; Courtiol et al, 2016; Grandy, Garrett, Schmiedek, & Werkle‐Bergner, 2016; Kosciessa et al, 2019; Kuntzelman, Jack Rhodes, Harrington, & Miskovic, 2018; see Figure 8). Indeed, this pattern also persists in other modalities, such as fMRI (e.g., Grandy et al, 2016; McDonough & Nashiro, 2014; McDonough & Siegel, 2018; Omidvarnia, Zalesky, Ville, Jackson, & Pedersen, 2019) or in simulation studies (e.g., Courtiol et al, 2016; Grandy et al, 2016; Kuntzelman et al, 2018). For our dataset the mMSE values stabilized at the coarse‐grained time series for scale ε = 12.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…This left us with 295 subjects for further analysis, and 162 of them were females. All the participants were between the ages of 22-36, 58 were between the ages of [22][23][24][25]130 were between the ages of [26][27][28][29][30]104 were between the ages of 31-35, and 3 were 36 years old.…”
Section: Fmri Data Acquisition and Preprocessingmentioning
confidence: 99%